The Effectiveness of the Introduction, Connection, Application, Reflection, Extension (ICARE) Learning Model in Improving Higher Order Thinking Skills (HOTS) of Junior High School Students - Nikmah, Filda Khoirun; Singgih, Suwito; Muhlisin, Ahmad (Paedagogia: Jurnal Pendidikan, 2025)
The importance of higher order thinking skills (HOTS) in the 21st century is undeniable, but the fact is that students HOTS abilities in Indonesia are still low. This study aims to analyze the effectiveness of the Introduction, Connection, Application, Reflection, Extension (ICARE) learning model in enhancing students higher-order thinking skills (HOTS) at the junior high school level. The study adopts a quantitative approach using a quasi experimental method. The design employed is a nonequivalent control group design, involving two classes: an experimental group and a control group. The study was conducted in the seventh grade of SMP N 2 Mertoyudan, using purposive sampling for sample selection. The research instruments consisted of eight essay questions for the pretest and posttest, which had been validated for validity and reliability. Data were analyzed using the Independent Sample t-Test and N-Gain. The results of this study showed a significant difference in higher-order thinking skills between the experimental and control classes. Based on the Independent Sample t-Test, there was a clear difference in the posttest scores of both classes with a significance level of 0.000. Additionally, the average N-Gain score for the experimental class was 0.56, while the control class scored only 0.31. From these findings, it can be concluded that the ICARE model is effective in enhancing higher order thinking skills among junior high school students.